Effect of light perturbation on the photo-fermentative hydrogen production of biomass from giant reed. (1st June 2022) - Shui, Xuenan; Jiang, Danping; Zhang, Huan; Zhang, Xueting; Yang, Jiabin; Lei, Tingzhou; Chen, Zhou; Zhang, Quanguo
Abstract: This study aimed to propose a light perturbation strategy to break the balance of the photo-fermentation system, thereby promoting the growth and hydrogen production of photosynthetic bacteria (PSB). This experiment explored the light perturbation of different intensities (4000 Lux, 5000 Lux, 6000 Lux, and 7000 Lux) on the hydrogen production process of giant reed at different times (24 h and 36 h). Under the optimal conditions of 6000 Lux perturbation at 24 h, the cumulative hydrogen yield (HY) and hydrogen production rate (HPR) reached 124.3 mL/g TS and 5.3 mL/g TS/h, which were 19.5% and 26.2% higher than no perturbation, respectively. Moreover, light perturbation at 24 h (1.02 g/L) and 36 h (1.025 g/L) significantly (p < 0.05) increased the dry weight of bacteria, which were 5.5% and 3.9% higher than no perturbation, respectively. In addition, based on matrix scatter analysis, the relationship between the hydrogen production rate after perturbation and the cumulative hydrogen production was the closest. The timing supplemental illumination was a useful approach for enhanced hydrogen yield of photo-fermentation, providing a new way for efficient use of lignocellulosic biomass clean production of hydrogen energy and the industrial promotion of hydrogen production via photo-fermentation. Highlights: Light perturbation was firstly performed in PFHP. The dry weight of bacteria was significantly increased by light perturbation. Biohydrogen yield of 123.4 mL/g TS was achieved via light perturbation at 24h. Light perturbation was beneficial to smooth the cumulation of VFAs.